The social construction of obesity in New Zealand prime time television media : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Raphael, Deborah (Massey University, 2008)
Obesity is an issue that has always been associated with morality, however in more recent times it has become defined as a health problem (or disease) of epidemic proportions. The construction of obesity as a problem is partly associated with the eternal quest for thinness. Media representations play a role in the construction of obesity and may be increasingly influential as media is becoming more and more prevalent in Western society. Furthermore, media have been shown to have considerable influence in affecting health behaviours and body image. Previous research has shown that media representations of obesity have been predominately negative and obese people are underrepresented in most types of television programming. The goal of this research was to discover how obesity is socially constructed in New Zealand prime time television. Data was collected over the period of a month, forming a synthetic week of recorded television programming that covered the prime viewing period between 6.00pm to 10.30pm. A discourse analytical approach was used to identify three main themes, morality medicalisation, and factual versus fictional. The moral theme involved discourses in which moral judgements were made about obese individuals, on both their character and actions, generally positioning the obese person as morally lacking. The medicalisation theme contained discourses around obesity as a health issue that constructed health issues as the fault of the individual which could be solved only one way- by losing weight. This functioned to position obese people as sick or unhealthy. The third theme, factual versus fiction presents the differences found between depictions of fictional obese characters and real people on television. Overall, obesity was found to be constructed negatively in television media. On television, the obese person is one which is either invisible, or is the object of moral judgements about the obese individuals worth as a person and their perceived poor health. Television representations of obesity, in some part, lead to the marginalisation of obese people. However the loathing for excess weight has been around for centuries and is so deeply ingrained in public discourse that to make a difference in how obese people are seen and treated, there would have to be a change in how society thinks about obesity, not just in how the media portrays obese people.
Keywords: Television broadcasting; New Zealand; Stereotypes in mass media; Obesity in mass media; Social psychology